Development of Selective Media for Komagataeibacter intermedius and Dekkera bruxellensis from a Mixed Culture - Ferren Pratama; Putu Virgina Partha Devanthi; Katherine Kho (Nusantara Science and Technology Proceedings, 2021)
Komagataeibacter intermedius and Dekkera bruxellensis are some of the most commonly found bacteria and yeast, respectively, during Kombucha fermentation. The development of selective media for separating both species is essential to make an accurate cell enumeration. This study aimed to develop a selective media for the enumeration of K. intermedius and D. bruxellensis from a mixed culture sample. Hestrin and Schramm (HS) agar and Potato Dextrose Agar (PDA) were chosen as the enumeration media for K. intermedius and D. bruxellensis, respectively. To select for K. intermedius, HS agar was added with various concentrations of cycloheximide (0, 1, and 10 mg/mL), NaCl (2% and 5%), and acetic acid (1%). To select for D. bruxellensis, PDA was added with various concentrations of chloramphenicol (0, 0.3, and 3 ?g/mL) and NaCl (2% and 5%). Each culture (~106 log CFU/mL) was serially diluted and plated on the respective agar media, followed by incubation at 30°C for 1-6 days. The results showed that PDA containing 2% NaCl could completely suppress K. intermedius growth while permitting complete recovery of D. bruxellensis. However, it took 6 days until visible growth was observed by D. bruxellensis. Moreover, HS with the addition of 1% acetic acid successfully inhibited D.bruxellensis while allowing the complete recovery of K. intermedius. The findings suggested that the two media were suitable for separating K. intermedius and D. bruxellensis on agar media, thus allowing a more accurate cell counting in studies involving the mixed cultures of both species.